AGN feedback in galaxy formation : proceedings of the workshop held in Vulcano, Italy, May 18--22, 2008 - Antonuccio-Delogu, V. (Vincenzo), 1960-; Silk, Joseph, 1942-; Cambridge eBooks (Cambridge : Cambridge University Press, 2011)
During the past decade, convincing evidence has been accumulated concerning the effect of active galactic nuclei (AGN) activity on the internal and external environment of their host galaxies. Featuring contributions from well-respected researchers in the field, and bringing together work by specialists in both galaxy formation and AGN, this volume addresses a number of key questions about AGN feedback in the context of galaxy formation. The topics covered include downsizing and star-formation time scales in massive elliptical galaxies, the connection between the epochs of supermassive black hole growth and galaxy formation and the question of whether AGN and star formation coexist. Authors also discuss key challenging computational problems, including jet-interstellar/intergalactic medium interactions, and both jet- and merging-induced star formation. Suitable for researchers and graduate students in astrophysics, this volume reflects the engaging and lively discussions taking place in this emerging field of research.
The effect of mass and star-formation timescale on galaxy evolution / C.D. Harrison and M. Colless -- Suppressing cluster cooling flows by multiple AGN activity / A. Nusser -- Starburst and AGN activity in Spitzer-selected sources at high-z / M. Polletta [and others] -- Star formation in galaxies hosting active galactic nuclei up to z~1 / J.D. Silverman, zCOSMOS and XMM-COSMOS -- The symbiosis between galaxies and SMBHs / G.L. Granato [and others] -- On the origin of halo assembly bias / A. Keselman -- AGN, downsizing and galaxy bimodality / M.J. Stringer [and others] -- Interaction and gas outflows in radio-loud AGN: disruptive and constructive effects of radio jets / R. Morganti -- Young radio sources: evolution and broad-band emission / L. Ostorero [and others] -- The duty cycle of radio galaxies and AGN feedback / S. Shabala -- Environment or outflows?: new insight into the origin of narrow associated QSO absorbers / V. Wild -- Physical models of AGN feedback / V. Antonuccio-Delogu [and others] -- Large-scale expansion of AGN outflows in a cosmological volume / P. Barai -- Relativistic jets and the inhomogeneous interstellar medium / G.V. Bicknell, J.L. Cooper and R.S. Sutherland -- AGN feedback effect on intracluster medium properties from galaxy clusters hydrodynamical simulations / D. Fabjan [and others] -- Physics and fate of jet-related emission line regions / M.G.H. Krause and V. Gaibler -- Cusp-core dichotomy of ellitpical galaxies: the role of thermal evaporation / C. Nipoti.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Galaxies -- Evolution -- Mathematical models -- Congresses; Galaxies -- Formation -- Mathematical models -- Congresses; Galactic nuclei -- Congresses; Electronic books